Exercise technique: Applying the hexagonal bar to strength and power training. - Lockie, R. G.; Lazar, A. (Strength and Conditioning Journal, 2017)
The hexagonal (hex) bar can often be found in training facilities; this article will describe how this equipment could be incorporated in the strength and power training of athletes. The unique bar design means that the hex bar could be used for different exercises, including the deadlift, farmer's walk, and jump squat. The literature regarding these exercises will be discussed, and this information will be used to demonstrate practical application for the strength and conditioning professional. In addition, the required execution for the low- and high-handle hex bar deadlift, hex bar farmer's walk, and hex bar jump squat will be documented.